Entre cartas e escritos: a trajetória do Padre Gabriel Malagrida e o Seminário Jesuíta da Parahyba (Séculos XVII e XVIII) - Medeiros, Thiago Gomes (2017)
This master thesis analyses the Gabriel Malagrida’s (1689-1761) trajectory in the Society of Jesus, having as reference the culture of the Baroque and the rules of the Ignatian charism to understand his religious life and missionary activity in colonial Brazil in the first half of 18th century. For this, it’s necessary to return to the bases of his instructional and doctrinal formation, which offer the initial support for the analysis of its baroque behaviour and the main unfolding of this culture in its Jesuitism in his daily practices. Baroque culture helps translate the performance of the religious in eighteenthcentury Brazil as a missionary, teacher, preacher, and also as a rebel. At the same time, the research has focused on the period in which Malagrida has continued to work in the New World, verifying his role in the Paraiba Captaincy with the construction of the Jesuit Seminary for the formation of priests, annexed to the São Gonçalo School, under the molds and aspirations of the Trent Council. In this sense, the text analyses the vicissitudes that converged on the shortage of priests and a school that instructed the children of the local settlers, in the late 17th century and in the first half of the 18th century, thus motivating requests of the Captains-Mores, Chamber’s Senate and of the ecclesiastical authorities to the Portuguese Crown, requiring the necessary conditions for the Ignatians to settle in the Captaincy, to act in the missions, to establish a school and, later, the seminary, attending to the requests of the inhabitants of the same captaincy. It will also be studied the antijesuitism during government of the Marquis of Pombal and the persecutory motivations against the Jesus Company. Finally, the life of Gabriel Malagrida; the process of creating the Paraiba Seminary; and the expulsion of the Jesuits from Paraiba in 1759 are the main points for the construction of this historical narrative.